The Urgency of Intellectual Property Rights Protection for MSMEs in the Creative Economy Era - Rahayu, Ade Lutfia; Arief, Anggreany; Asriati, Asriati (ADVANCED PRIVATE LEGAL INSIGHTS, 2025)
The aim of this research was to determine and analyze the effectiveness of legal protection of intellectual property rights of micro, small, and medium enterprises in the creative economy sector, as well as to determine the factors that influence the effectiveness of legal protection of intellectual property rights holders of micro, small, and medium enterprises in the creative economy sector. This research method uses an empirical research method. And the results of this study indicate that the level of effectiveness of the implementation of legal protection of intellectual property rights of micro, small, and medium enterprises in the creative economy sector is categorized as quite effective but not optimal due to limitations in terms of preventing plagiarism in terms of protecting copyright and trademarks. The factors that influence effectiveness include several aspects, namely access to information and technology, complex costs and procedures, legal substance, and awareness and knowledge of MSME actors. The recommendations in this study are that collaboration is needed in public education efforts to increase public awareness, improve regulations, and enforce strict laws and that public education and socialization with a wider reach are needed regarding the importance of Intellectual Property Rights as an effort to build public awareness and concern.